Analysis of social factors and their relationship with perceived risk for e-commerce purchases (2017)
Many purchasing decisions have an associated level of risk deriving from the uncertain environment facing the buyer and the possible negative consequences of an online purchase. Through an empirical study, using a regression analysis of latent variables and the ordinary Partial Least Squares (PLS) optimization technique, a model that represents the relationship between customer orientation, social influence, reputation, privacy and how they affect the perceived risk, is proposed. The purpose of this is to enable companies to develop more effective methods of reducing this barrier and create strategies to increase purchases through e-commerce.